Design of Behavioral Counseling Service Implementation Using Modeling Techniques to Increase Self Confidence (Descriptive Analysis Study on Class XI Students. F S SMA PGRI 2 Padang) - Salsabilla, Aulia Nur; Kasih, Fitria; Nita, Rahma Wira (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
This research is motivated by the existence of problems about self-confidence. The purpose is to describe: 1.) The description of self confidence of students in class XI.F S SMA PGRI 2 Padang. 2.) The design of the implementation of behavioral counseling services using modeling techniques to increase self-confidence. This type of research is descriptive analysis. The population in this study were students in class XI. F S at SMA PGRI 2 Padang who have self confidence which amounted to 30 people. Sampling using purposive sampling technique, namely students with a total of 3 people. Data collection tools in the form of a questionnaire, then analyzed using percentage classification. The results of the study revealed that: 1.) The description of students' self-confidence in class XI.F S SMA PGRI 2 Padang, is in the low criteria. 2.) Behavioral counseling service implementation plan using modeling techniques to increase self confidence. Based on the results of this study, it is recommended to the counseling teacher to be able to use the implementation of behavioral counseling using modeling techniques to increase self confidence in the future.